Rola wniosków i opinii społeczności lokalnych w procesie podejmowania przez organy samorządu terytorialnego decyzji środowiskowych w sprawach inwestycji w ochronie środowiska . - Szkotnicka, Iwona Małgorzata (Kwartalnik Prawa Publicznego, 2017)
The paper presents the problem of public participation in the process of making the environmental decisions by local self-governments authorities in matters of investments in environmental protection, which is ensured by the provisions of the Act of 3 October 2008 on sharing information about the environment and its protection, public participation in its protection and on environmental impact assessments. Ensuring this participation is important in the process of correct making the environmental decisions by local self-governments authorities concerning of investments in environmental protection.